Effect of Total Quality Management, Performance Measurement System, Reward System, and Management Control System on Unit Manager Performance - Noer Sasongko; Sinta Khusniya (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effect of total quality management, performance measurement system, reward system, and management control system on the performance of unit managers at RSU Fastabiq Sehat PKU Muhammadiyah Pati. The method of data collection in this study was a questionnaire filled out by respondents, namely unit managers who worked at RSU Fastabiq Sehat PKU Muhammadiyah Pati. Sampling of 30 respondents in this study using purposive sampling method. The results of this study reveal that: (1) total quality management has no significant effect on managerial performance. (2) the performance measurement system has an effect on managerial performance. (3) the reward system has no effect on managerial performance. (4) the management control system has an effect on managerial performance.